Extratos das folhas de café e de seus principais compostos bioativos: avaliação do estresse oxidativo - Nascimento, Gerlan Oliveira do (2022)
Coffee leaves are a significant source of polyphenolic compounds that may be useful in reducing hyperglycemia and dyslipidemia. The present study focused on investigating the antioxidant, antiglycemic activities, digestive enzyme inhibition, bioaccessibility and hypoglycemic effect. The content of biocompounds after different ways of drying the leaves was also investigated in addition to the search for metallic traces, as these may be related to the plant's defense against the coffee tree disease (rust). The identification and quantification of the main metabolites of the extracts was done by High Performance Liquid Chromatography. The Folin-Ciocalteu method was used to determine the Total Phenolic Content and the antioxidant activities by capturing the DPPH•, O2•-, ROO• radicals and the H2O2 and HOCℓ molecules. The extraction of the metals Aℓ, Cu, Mg, Mn, Ni, Sn and Zn for further quantification by Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) was performed using an acid mixture in a digester block. The extracts were analyzed for inhibition of α-glucosidase and pancreatic lipase, antiglycating activity by spectrofluorescence technique, bioaccessibility by in vitro digestion and hyperglycemia by zebrafish model. Chromatographic analysis elucidated a chemical profile characterized by three classes of polyphenols (xanthone, chlorogenic acid and flavonoids) and caffeine. The antioxidant capacity of the extracts was higher than the positive controls and the TPC was 608.70 ± 0.02 mg GAE g–1. Coffee leaves showed strong inhibition of α-glucosidase (IC50 = 40.30 μg mL–1) greater than the isolated metabolites and acarbose, and inhibited pancreatic lipase (IC50 = 56.43 μg mL–1) possessing also, hypoglycemic effect in zebrafish similar to acarbose and metformin. In addition, fluorescence reduction was observed implying antiglycemic effect. With the exception of rutin, all biocompounds were detected in all digestion steps. The relationship between metals and biocomposites allowed us to discriminate resistant from susceptible coffee trees. Finally, the results suggest that C. arabica leaf extracts possess antidiabetic and anti-obesity properties that can be attributed to the main metabolites and the synergistic action between them.